Mechanical work accounts for sex differences in fatigue during repeated sprints - Billaut, F.; Bishop, D. J. (European Journal of Applied Physiology, 2012)
To investigate whether the larger reduction in mechanical work observed during repeated-sprint exercise (RSE) in men versus women represents a true, physiological sex dimorphism or is the consequence of the higher initial mechanical work performed by men. Male and female team-sport athletes (n = 35) performed 20, 5-s cycle sprints interspersed with 25 s of rest. Mechanical work and surface electromyograms (EMG) of four muscles were recorded in every sprint. Mechanical work achieved in one sprint (20.7%, P = 0.0006), total work accumulated over the 20 sprints (21.1%, P = 0.009) and percent work decrement (32.2%, P = 0.008) were larger in men than in women. When both sexes were plotted together, there was a positive relationship between the initial-sprint work and the work decrement across sprint repetitions (r = 0.89, P = 0.002). The RSE induced larger (P = 0.009) absolute EMG amplitude changes in men (-155.2 ± 60.3 mVs) than in women (-102.5 ± 45.1 mVs). Interestingly, in a subset of men and women (n = 7 per group) matched for initial-sprint work, the sex difference in percent work decrement (men: -29.5 ± 1.5%; women: -27.2 ± 3.2%; P = 0.72) and EMG changes (men: -17.7 ± 6.9% vs. women: -15.3 ± 7.1%; P = 0.69) no longer persisted. Results show that the proposed greater fatigue in men is likely to be a consequence of their greater absolute initial-sprint performance, rather than a sex difference in fatigue resistance per se. We conclude that, on the basis of the absolute mechanical work completed, women are not more fatigue resistant than men and use comparable muscle recruitment strategies to perform RSE.